2022
DOI: 10.1016/j.jesp.2021.104230
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes behind the shooter bias: Dissecting response bias, motor preparation and information accumulation

Abstract: A rich body of research points to racial biases in so-called police officer dilemma tasks: participants are generally faster and less error-prone to "shoot" (vs. not "shoot") Black (vs. White) targets. In three experimental (and two supplemental) studies (total N = 914), we aimed at examining the cognitive processes underlying these findings under fully standardized conditions. To be able to dissect a-priori decision bias, biased information processing and motor preparation, we rendered video sequences of virt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Of additional interest, using a different methodology to investigate stereotype-based responding—notably, the shooter task (Correll et al, 2002 )—Frenken et al ( 2022 ) recently traced the origin of stereotype bias to differences in non-decisional processes, specifically motoric preparation (i.e., primes pre-activate stereotype-consistent motor responses, thus enhance execution readiness). Accordingly, in both the gender-classification and stereotype-status task, here we also considered the possibility that task performance may be underpinned by differences in non-decisional processing operations (Voss et al, 2013a , 2013b ).…”
Section: The Current Researchmentioning
confidence: 99%
“…Of additional interest, using a different methodology to investigate stereotype-based responding—notably, the shooter task (Correll et al, 2002 )—Frenken et al ( 2022 ) recently traced the origin of stereotype bias to differences in non-decisional processes, specifically motoric preparation (i.e., primes pre-activate stereotype-consistent motor responses, thus enhance execution readiness). Accordingly, in both the gender-classification and stereotype-status task, here we also considered the possibility that task performance may be underpinned by differences in non-decisional processing operations (Voss et al, 2013a , 2013b ).…”
Section: The Current Researchmentioning
confidence: 99%
“…It is therefore unclear how well the findings by Pickel and Sneyd ( 2018 ), obtained from a Midwestern U.S. population, generalize to other cultures. Recent results by Frenken et al ( 2022 ) suggest that similar racial stereotypes exist in Germany. Frenken et al ( 2022 ) used a computer-based first-person shooter task (Correll et al, 2002 ) for which several U.S. studies have found that participants are quicker to “shoot” armed Black actors compared with White ones and slower to indicate a “don’t shoot” response for unarmed Black actors (Mekawi & Bresin, 2015 ).…”
mentioning
confidence: 94%
“…Frenken et al ( 2022 ) used a computer-based first-person shooter task (Correll et al, 2002 ) for which several U.S. studies have found that participants are quicker to “shoot” armed Black actors compared with White ones and slower to indicate a “don’t shoot” response for unarmed Black actors (Mekawi & Bresin, 2015 ). Frenken et al ( 2022 ) found that this racial bias generalizes to German participants.…”
mentioning
confidence: 99%